STRATEGI PEMASARAN EKOWISATA BAHARI PULAU HOGA TAMAN NASIONAL WAKATOBI PROVINSI SULAWESI TENGGARA - Nurhidayati Nurhidayati (Jurnal Riset Bisnis Indonesia, 2014)
This study aims to examine and analyze the effect of product, price, promotion, place, people, andphysical evidence to the satisfaction of visitors. Issue raised in this research is how to influence theproduct, price, promotion, place, people, and physical evidence of an effect on visitor satisfaction onHoga Island attractions. In this study using a kind of explanatory research is a study conducted toexplain the causal relationship between the variables and testing hypothesis. In this case describesthe influence of relationship marketing mix which includes product, price, promotion, place, peopleand the physical evidence to the satisfaction of the visitor attraction Hoga Island Wakatobi NationalPark. The study was conducted by survey method distributing questionnaires to135 visitor attractions in Hoga Island. Sampling studies using accidental sampling technique that is committedagainst a person or object encountered by chance there. The result shows that the product, price,promotion, place, people and physical evidence significantly influence visitor satisfaction in HogaIsland attractions.Keywords: Marketing Mix, Physical Evidence, Visitor Satisfaction.